2013
DOI: 10.18433/j3cw23
|View full text |Cite
|
Sign up to set email alerts
|

Alkylphospholipids – A Promising Class of Chemotherapeutic Agents with a Broad Pharmacological Spectrum

Abstract: -PURPOSE:Since when alkylphospholipds (ALPs) were discovered and, even further after miltefosine's approval for the treatment of cutaneous metastasis of breast cancer and leishmaniasis, their activity against many other diseases have been extensively studied. This review aims to provide a summary of the alkylphospholipids' applications investigated so far. RESULTS: The mechanism of action of ALPs is not fully understood, however it is believed that they interfere with lipid homeostasis leading to cell apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 132 publications
1
13
0
3
Order By: Relevance
“…Cells treated with edelfosine exhibited a marked and rapid decrease in p-Akt Ser473 levels, coupled with a reduction in the phosphorylation levels of mTOR (p-mTOR) ( 95 ). Its clinical use is limited by the high toxicity and low selectivity ( 96 ). The thioether analog of edelfosine, ilmofosine (BM 41.440) has demonstrated dose-dependent in vivo and in vitro antitumor activity in various solid tumor models.…”
Section: Allosteric Inhibitorsmentioning
confidence: 99%
“…Cells treated with edelfosine exhibited a marked and rapid decrease in p-Akt Ser473 levels, coupled with a reduction in the phosphorylation levels of mTOR (p-mTOR) ( 95 ). Its clinical use is limited by the high toxicity and low selectivity ( 96 ). The thioether analog of edelfosine, ilmofosine (BM 41.440) has demonstrated dose-dependent in vivo and in vitro antitumor activity in various solid tumor models.…”
Section: Allosteric Inhibitorsmentioning
confidence: 99%
“…In a review study, Cota et al (de Almeida Pachioni et al , 2013) reported that, according to available data, there was a higher mortality rate among patients treated with Sb v than in those treated with amphotericin B. In the countries of Ethiopia, India and Spain, liposomal amphotericin B was the drug used to treat 605 (65%) coinfected patients, with the lowest number, 149 (16%), of the use of Sb v or miltefosine, 143 (15%).…”
Section: Discussionmentioning
confidence: 99%
“…MT inhibits the biosynthesis of phosphatidylcholine, thus affecting phospholipid biosynthesis [79,103]. The proposed mechanism of action firstly involves the binding to cell membrane, followed by the internalization through two membrane proteins: L. donovani miltefosine transporter ( Ld MT), a member of the P4-ATPase subfamily; and a potential noncatalytic β subunit of Ld MT ( Ld Ros3) [97,104].…”
Section: Antileishmanial Drug Resistancementioning
confidence: 99%